Analysis of Diagnostic Information on Head CT Scan with Modifications Scanogram as an Efforts to Decrease the Radiation Dose to The Eyes - Jeffri Ardiyanto; Rini Indrati; Bagus Dwi Handoko (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The purpose of this study was to determine the work of CT head scanogram modification to avoid radiation to the eyes towards the results of diagnostic information and pathological abnormalities. It is an experimental research with observational approach. The results show that the modification scanogram on head CT with slices parallel to the supra orbito meatal line (SOML) can avoid the radiation dose to the eyes. Anatomical information that is visible from 30 scanning produces an average value of 2.57 or obvious, and may reveal abnormalities in the head with obvious pathological.